Penyuluhan Kesehatan Jiwa Pada Pasien ODGJ Depresi di Bumi Ayu Kota Bengkulu 2023 - Fitrianti, Cici; Yanti, Defri; Anestin, Lala; Pratama, Geri; Apriani, Letty; Cahyani, Afrilen Afiva; Direja, Ade Herman Surya (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Mental health is a health problem that is a priority in the world, including in Indonesia. Depression can attack anyone regardless of gender or age group. The aim of this community service is to help patients with symptoms of depression increase their knowledge of how to control emotions well and have good thought patterns and practice patience in all daily activities. The implementation method for this activity is mental health education for ODGJ with depression disorders which is carried out in Bumi Ayu, Bengkulu City. The data collection technique used is the interview technique. Meanwhile, the time for this community service was carried out in October 2023. The result of this community service is that after carrying out this activity, you can find out how to carry out self-care by straightening the client's clothes, cutting nails, and washing the face so that they can done independently. Patients are trained to carry out self-care as taught or not to carry out self-care deficits. Shows that the factors a person is affected by depression are; there are problems at the emotional level, genetic factors, stress and pressure, and have medical problems.